2020
DOI: 10.31236/osf.io/wugcr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic Review of the use of “Magnitude-Based Inference” in Sports Science and Medicine

Abstract: Magnitude-based inference (MBI) is a controversial statistical method that has been used in hundreds of papers in sports science despite criticism from statisticians. To better understand how this method has been applied in practice, we systematically reviewed 232 papers that used MBI. We extracted data on study design, sample size, and choice of MBI settings and parameters. Median sample size was 10 per group (interquartile range, IQR: 8 – 15) for multi-group studies and 14 (IQR: 10 – 24) for single-group stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…However, it is worth noting that these conclusions were based on inferences made using magnitude based inferences (MBI), with ‘most likely positive’ and ‘likely positive’ effects of CHO supplementation reported for peak power and tiredness, respectively. The MBI approach has recently received substantial scrutiny for failing to adequately control type 1 error rates (i.e., false positives), particularly for effects characterised as ‘likely’ [ 33 ]. Furthermore, the study of Pomportes et al [ 18 ] also reported (alongside MBI) no significant effect on either variable when assessed using a repeated measures ANOVA.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that these conclusions were based on inferences made using magnitude based inferences (MBI), with ‘most likely positive’ and ‘likely positive’ effects of CHO supplementation reported for peak power and tiredness, respectively. The MBI approach has recently received substantial scrutiny for failing to adequately control type 1 error rates (i.e., false positives), particularly for effects characterised as ‘likely’ [ 33 ]. Furthermore, the study of Pomportes et al [ 18 ] also reported (alongside MBI) no significant effect on either variable when assessed using a repeated measures ANOVA.…”
Section: Discussionmentioning
confidence: 99%
“…But the paper depends on a statistical method called measurement based inference (MBI), which statisticians have widely criticized as misleading and incoherent, producing high rates of false positive findings (Sainani, 2018). A re-examination of the data from the foam rolling study using more rigorous statistical testing casts doubts on many of their claims (Lohse et al, 2020). Over the years, hundreds of published papers in the discipline of sports science have used MBI, and the unsoundness of the method throws many of these results into doubt (Lohse et al, 2020).…”
Section: Mbi and The Persistence Of Poor Methodology In Sports Sciencementioning
confidence: 99%
“…A re-examination of the data from the foam rolling study using more rigorous statistical testing casts doubts on many of their claims (Lohse et al, 2020). Over the years, hundreds of published papers in the discipline of sports science have used MBI, and the unsoundness of the method throws many of these results into doubt (Lohse et al, 2020). The method was introduced in a 2006 paper by the sports scientists Alan Batterham and Will Hopkins (Batterham and Hopkins, 2006) with the intent of supplanting standard frequentist statistical practices.…”
Section: Mbi and The Persistence Of Poor Methodology In Sports Sciencementioning
confidence: 99%
See 1 more Smart Citation
“… 54 The problem may be compounded when poor statistical techniques are passed from mentors to students, thus propagating poor practices to the next generation of researchers. 55 Finally, a lack of statistical expertise in the journal peer review process means that many papers are published using suboptimal statistical methods; 52 this often creates a positive feedback loop as methods are copied from paper to paper. BJSM (British Journal of Sports Medicine) only began having statistical Deputy Editors in 2019.…”
Section: Barriers To Collaborationmentioning
confidence: 99%